Determination of Stunting Handling Policy on Enggano Island as One of The Outer Islands - Jatmiko Yogopriyatno; Sartika Sartika (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
This research focuses on the implementation of stunting prevention policies in Enggano Island, North Bengkulu Regency, with special attention to policy determinants in remote areas. To understand the complexity and dynamics of interactions between factors that influence the success of health policies in this hard-to-reach area, this research uses a qualitative explanatory approach with case study methods and dynamic system modeling. The results show that the success in reducing stunting rates on Enggano Island cannot be separated from the active involvement of various parties, including the government, health workers, and community leaders, who all work together in monitoring, educating, and providing additional food to children at risk of stunting. In addition, utilizing local wisdom has been shown to play an important role in strengthening households' adaptive capacity to this health problem, which in turn contributes to reducing stunting rates. Policy support complemented by good management also allows for more effective collaboration between actors, thus facilitating policy implementation. This research provides new insights into the importance of integrating local values and cross-sectoral cooperation in addressing health challenges in remote areas. The findings also emphasize that a holistic and adaptive policy approach is necessary for successful stunting management, especially in areas with limited access and resources.